Strategi Domestikasi Ikan Gabus (Channa Striata) Berdasarkan Aspek Iktiologi: Review Tantangan Dan Potensi Akuakultur - Reni Hesti Mentari; Mira Atul Hayati (Jurnal Sains Pertanian, 2026)
Snakehead fish (Channa striata) is a freshwater fishery commodity with high economic value due to its albumin content, which is beneficial for health. However, dependence on wild catches has led to a decline in its population. Domestication is a key strategy to ensure sustainable production through aquaculture. This review aims to analyze the domestication strategies for snakehead fish based on ichthyological aspects, including morphology, feeding habits, reproduction, and behavior. The main challenges in domestication include high cannibalism during the seed stage and the difficulty of transitioning from natural to artificial feed. Feed management approaches with a frequency of 3-4 times daily and the use of natural feeds such as Daphnia sp. and Tubifex sp. have proven effective in increasing survival rates up to 95%. The potential for intensive systems like raceway farming also shows promising biological and economic feasibility. Through the integration of controlled hatchery technology and hormonal manipulation, snakehead fish domestication is expected to support the independence of the national aquaculture industry. Keywords: Channa striata; domestication; ichthyology; cannibalism; albumin